Teachers' Efforts to Implement Honest Character in Class IV Students of Lawe Kongker State Elementary School, Southeast Aceh Regency - Erasni, Naji Pitri; Ahadin, Ahadin; Fauzi, Fauzi (Universitas Syiah Kuala, 2024)
This research aims to describe how teachers try to implement honest character in class IV students at Lawe Kongker State Elementary School, Southeast Aceh Regency. This research uses a qualitative approach with descriptive research type. The subjects in this research were teachers and students of class IV at Lawe Kongker State Elementary School, Southeast Aceh Regency. The data collection techniques used were observation and interviews. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Based on the discussion, the teacher's efforts to implement the honest character of class IV students are by teaching students to be honest when speaking, honest when interacting, true commitment, true in keeping promises, and true to who they are. Teachers continuously teach, guide, educate, train, advise, direct and accustom students to always be kind and honest to teachers, friends, parents and other people. The honest character can be applied to fourth grade students by providing class media in the form of honesty hours, advising, reprimanding, and controlling students when carrying out an activity both inside and outside the learning process. Students who have an honest and trustworthy character are very good and noble traits. The fourth grade teacher is firm and continues to provide motivation, encouragement and support to students so that they are not afraid to do good and honest actions even when admitting mistakes that have been made to others..